Morphological Variation and Beta Carotene Contents of Several Clones of Ubi Kuning Cassava Genotype Derived from Irradiated Shoot in vitro - Rahman, Nurhamidar; Supatmi, Supatmi; Fitriani, Hani; Hartati, N Sri (Jurnal ILMU DASAR, 2020)
In line with the increase in cassava production and the development of nutrient-rich cassava in order to support national food diversification and biofortification programs, the selection of selected varieties of cassava varieties, which are superior in nutrients especially rich in beta carotene is very necessary. Beta carotene is an important source of antioxidants to scavange free radicals and is a provitamin A precusor to form vitamin A. The development of superior cassava riching in beta carotene can be done through the mutation approach with gamma irradiation. The observation of changes in morphological characters and levels of beta carotene from irradiated cassava need to be done to get the superior beta carotene cassava clone candidates, which could be developed in the future. This experiment was conducted at the Biotechnology Research Center, LIPI. The sample used in this study originated from in vitro shoots from several Ubi Kuning clones resulting from 10 Gy radiation, which were then transferred to the field. Observations of morphological characters and levels of beta carotene of Ubi Kuning were carried out in the third generation, which was harvested at the age of 10 months. The morphological analysis of irradiated Ubi Kuning showed that there was a difference in the intensity of tuber color between some of irradiated Ubi Kuning clones compared to the control. The determination of beta carotene levels based on the standard beta carotene curve found that the highest content of beta carotene was found in the UK Rad 3.4 clone with beta carotene content of 0.252 μg / mL compared to the control (0.219 μg / mL). The lowest beta carotene content was obtained in UK Rad 3.3 (0.048 μg / mL), followed by UK Rad 3.2 (0.221 μg / mL) and UK Rad 4.1 (0.120 μg / mL). This shows that the irradiated Ubi Kuning at dosage of 10 Gy caused variations in the intensity of tuber colors and the content of beta carotene from the cassava.Keywords: Ubi Kuning, beta carotene, Gamma light irradiation